Pengaruh Attachment dan Harga Diri terhadap Regulasi Emosi Siswa - Mu'arifah, Alif; Muyana, Siti; Saputra, Wahyu Nanda Eka; Mohamad, Zhooriyati Sehu (Jurnal Kajian Bimbingan dan Konseling, 2020)
Emotion regulation is an important variable to support students’ optimal development. Students with high emotion regulation tend to minimize their aggressive behavior. However, some students have difficulty in regulating their emotions. Previous studies show that attachment and self-esteem influence emotion regulation. This study aims to examine the effect of the two variables on emotion regulation of students. 150 randomly selected students were involved in the study. Multiple linear regression was applied to analyze the research data. The results showed that there was a significant effect of attachments and self-esteem on emotion regulation. Attachment and self-esteem influence emotion regulation by 76.3% while other variables influence it by the remaining 23.7%. The result can be used as a basis for constructing guidance and counseling services that involve attachment and self-esteem to improve the emotion regulation of students.